Letterbook of major general Hugh Lyon (Lyle) Carmichael, Jan. 1810 - Sept., 1811. - Carmichael, Hugh Lyon (Lyle) (1811)
This letterbook was written by Major General Hugh Lyon (Lyle) Carmichael between January 1810 and September 1811. The letters deal with military affairs and written mainly from Mon Repos; Petite Montagne, Barbados and Demerarya; includes letters to Sir Alexander Cochrane and Sir George Beckwith. Statement of Major General Carmichael about expedition to St. Domingo.
NLJCols20082021
Keywords: Manuscripts -- Jamaica; Manuscripts; Jamaica